Update The Monetary And Financial Policies Transparency Code. (Policy Papers; Policy Paper ;, 2019)
The paper responds to a request made by the Executive Board at the time of the 2017 Review of the Standards and Codes Initiative (RSCI) for a revision and update of the 1999 Monetary and Financial Policies Transparency Code (MFPT). Directors asked staff that the new code remove the overlap on financial policies covered by other standards, expand the transparency standards to broader set of activities undertaken by many central banks since the Global Financial Crisis, and reorient the transparency standards to facilitate risk-based assessments to support policy effectiveness and address macroeconomic risks.